PERANAN KADAR HEMATOKRIT, JUMLAH TROMBOSIT DAN SEROLOGI IgG - IgM ANTIDHF DALAM MEMPREDIKSI TERJADINYA SYOK PADA PASIEN DEMAM BERDARAH DENGUE (DBD) DI RUMAH SAKIT ISLAM SITI HAJAR MATARAM - Taufik S, Ahmad; Yudhanto, Didit; Wajdi, Farid; -, Rohad (journal of internal medicine; Vol. 8, No. 2 Mei 2007)
The mortality rate of Dengue Haemorrhagic Fever is still high. It is still very difficult to predict shock. The common laboratory feature to predict shock are low platelet count, high hematocrit level and the positive result of serologic test (IgG and IgM antiDHF), but the validity remains controversial. This researh was determine many factor to predict shock in dengue hemoragik fever patient . This research was case-control study. Data was collected from secondary data based on hematologic and serologic findings of patients with DHF who were hospitalized in Siti Hajar Islamic Hospital Mataram in the period of June 1, 2005 until June 1, 2006. The samples of this study were patients that diagnosed as DHF based on WHO criteria and performed with rapid serologic test Pan Blow? made in America, for Ig G and Ig M anti DHF. DHF patients that suffering shock were catogorized as case group (n=47), and DHF patients without shock were control group (n=94). The total number of control group was two times of case group. Risk factor of shock were analyzed using chi-square test and multiple logistic regressions with level of significance of < 0.05. The number of samples used in this study were 141 patients diagnosed as DHF, there were 47 patiensts DHF with shok and 94 DHF patients without shock. There was 70% patient with thrombositopenia and 44% patient had high rate of hematokrit more than 41.5 %. Shock was more frequent among pasients age more than 25 years, male, hematokrit level less than 40% and platelet count 50,000-100,000/ml. Based on univariate analysis, age, gender, high hematocrit value and trombositopenia were not significantly different to predict shock. On multiple logistic regression methode, primery infection (IgM+ and IgG-) and secondary infection (IgG positif and IgM+/-) were not significantly different to predict shock. The conclusion of this study is high hematocrit value, platelet count and serology IgM or and IgG antiDHF there were no factor that could predict shock in DHF patients.
Keywords: Dengue Hemorrhagic Fever, IgG and IgM antiDHF, shock